Metode Pengeringan Terhadap Karakteristik Teh Daging Buah Pala Halus dan Lempengan - Andi Patimang; Suhartini, Wildan (Politeknik Negeri FakFak, 2024)
Tea is a drink that is often consumed by Indonesian people and has a refreshing effect. Generally, tea is made from young tea leaves that are picked and processed in such a way as to produce good quality tea. Apart from coming from tea leaves, tea can also be processed from other ingredients, one of which is nutmeg flesh. The purpose of this study was to determine the characteristics of the tea pulp of fine nutmeg and slabs by studying different drying methods. The design of this study used a completely randomized design (CRD). The drying method used is sun drying (SM), and 50° C oven. This study used the ANOVA test which was processed using excel. The results showed that the organoleptic characteristics (color, taste, and aroma) of ground nutmeg tea with the 50°C oven drying method were the best. The results of the organoleptic test of refined nutmeg tea and slabs for the sun-dried method (SM) and 50°C oven were as follows: color, taste, and aroma respectively for refined nutmeg tea oven 50°C 5.3; 6,2; and 6.7, nutmeg tea oven 50° C 5.5; 6; and 6.1, refined nutmeg tea SM 5.2; 6; And 6.1, tea nutmeg slabs SM 5.2; 5.7; and 5.9. The yield for SM drying was 12.57% and the yield for oven drying at 50° C was 7.20%, the water content and pH were in accordance with the Indonesian National Standard 3836:2013.